Modelling of wildfire impacts on catchment hydrology applied to two case studies. Issue 17 (25th March 2015) - Mahat, Vinod; Anderson, Axel; Silins, Uldis
Abstract We used a conceptual modelling approach on two western Canadian mountainous catchments that were burned in separate wildfires in 2003 to explore the potential of using modelling approaches to generalize post‐wildfire catchment hydrology in cases where pre‐wildfire hydrologic data were present or absent. The Fishtrap Creek case study (McLure fire, British Columbia) had a single gauged catchment with both pre‐fire and post‐fire data, whereas the Lost Creek case study (Lost Ck. fire, Alberta) had several instrumented burned and reference catchments providing streamflows and climate data only for the post‐wildfire period. Wildfire impacts on catchment hydrology were assessed by comparing pre‐wildfire and post‐wildfire model calibrated parameter sets for Fishtrap Creek (Fishtrap Ck.) and the calibrated parameters of two burned (South York Ck. and Lynx Ck.) and two unburned (Star Ck. and North York Ck.) catchments for Lost Ck. Model predicted streamflows for burned catchments were compared with unburned catchments (pre‐fire in the case of Fishtrap Ck. and unburned in the case of the Lost Ck.). Similarly, model predicted streamflows from unburned catchments were compared with burned catchments (post‐fire in the case of Fishtrap Ck. and burned in the case of the Lost Ck.). For Fishtrap Ck., different model parameters and streamflow behaviour were observed for pre‐wildfire and post‐wildfire conditions. However, the burned and unburned model results from the Lost Ck. wildfire did not show differing streamflow responses to the wildfire. We found that this hydrological modelling approach is suitable where pre‐wildfire and post‐wildfire data are available but may provide limited additional insights where pre‐disturbance hydrologic data are unavailable. This may in part be because the conceptual modelling approach does not represent the physical catchment processes, whereas a physically based model may still provide insights into catchment hydrological response in these situations. Copyright © 2015 John Wiley & Sons, Ltd.